Effect of different topography to the yield performance of the oil palm / Nur Farhana Arifin - Arifin, Nur Farhana (Faculty of Plantation and Agrotechnology, 2016)
This case study presents about the yield productivity of the oil palm in different types of topography between two different area. Different type of topography consists of flat area, undulating area and also hilly area. Three years data is use in this case study from July 2014 until June 2016.The objectives of this case study are to determine the difference in yield productivity in the three types of topography between two areas and evaluate the yield production of the oil palm in different types of topography (flat, undulating and hilly area). This case study showed that there is a significant difference of the yield per hectare in the three types of topography for both areas. In Area 1 and area 2 , undulating area has the highest mean productivity of yield which are 498.91 mt/ha and 386.72mt/ha. Followed by hilly area which is 129.78 mt/ha and in third place was flat area, 55.875 mt/ha for Area 1. In Area 2, second place is flat area which is 169.64 mt/ha and followed by hilly area, 122.21 mt/ha. Then, there are significant difference between the yield productivity and types of topography in flat and undulating area where the P-value is 0.000 less than 0.05 (P≤0.05) but there is no significant different in hilly area because the P-value is 0.492 more than 0.05 (P-value≥0.05)